Psoriatic spondyloarthropathy: a long term prospective study. - Hanly, J G (1988)
Fifty two patients with psoriatic spondyloarthropathy were monitored prospectively over a mean of 57 months (range 30-107). A comprehensive protocol was used to assess clinical and radiological features of disease activity and severity. Serial radiographs showed a significant increase in the number of patients with syndesmophyte formation and sacroiliitis. In contrast, there was no significant increase in the number of patients with inflammatory neck pain or stiffness, back pain or stiffness, cervical spine limitation, or sacroiliac tenderness. Similarly, there were no significant changes in any of the direct or indirect measurements of thoracolumbar spine mobility. The presence of HLA-B27 did not appear to influence disease progression. These results suggest that although patients with psoriatic spondyloarthropathy have radiological progression of their disease, this remains clinically silent and does not compromise spinal mobility.